Bidirectional Quadratic Converter-Based PMBLDC Motor Drive for LEV Application - Mukesh Kumar; Kalpana Chaudhary; R. K. Saket; Baseem Khan (Journal of Electrical and Computer Engineering)
In this study, a bidirectional DC-to-DC quadratic converter (BDQC) is designed and developed for the motoring and regenerative braking (RB) of a permanent magnet brushless DC (PMBLDC) motor for a light electric vehicle (LEV) application. A PMBLDC motor is deemed more suitable for an electric vehicle (EV) due to its high efficiency and torque density. In the present work, a BDQC of 1 kW is designed to drive a 1.1 HP PMBLDC motor through a conventional voltage source inverter (VSI). An EV’s load cycle is emulated using a highly inertial load driven by a PMBLDC motor during the converter’s boost mode operation. RB is a crucial factor in extending the driving range of EVs by efficiently utilizing battery power. The converter operates in buck mode during RB, and simultaneously, the back electromotive force (EMF) of the PMBLDC machine is boosted by the self-inductance of the PMBLDC motor and the VSI. The braking technique used in this work eliminates the traditional drawback of RB in buck mode, as the power is extracted even when the motor’s back EMF is lower than the battery’s voltage. The control strategy has been implemented using the TMS320F28335 DSP controller for a developed converter prototype of the converter and driving the PMBLDC motor. The experimental results are compared to the simulation results, and a good alignment has been found.